2009
DOI: 10.1016/j.aquaculture.2008.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, plasma cortisol and effectiveness of benzocaine, MS-222 and isoeugenol measured in individual dorsal aorta-cannulated Atlantic salmon (Salmo salar) following bath administration

Abstract: During the life cycle as farmed animals there are numerous situations where fish are subjected to handling and confinement. Netting, weighing, sorting, vaccination, transport and, at the end, slaughter are common events under farming conditions. As research animals fish may also undergo surgical procedures, ranging from tagging, sampling, and small incisions, to larger operations. Under these varying situations treatment with anaesthetic agents might be necessary in order to ensure the welfare of the fish. Ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
90
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(98 citation statements)
references
References 174 publications
(281 reference statements)
6
90
2
Order By: Relevance
“…Silver catfish exposed to EOO before handling had a better recovery profile of these parameters, as lower or similar concentrations were detected at 8 h compared to 0 h. A similar pattern was verified in the cortisol levels in Atlantic salmon following bath administration with benzocaine, MS-222, and isoeugenol. After 360 minutes, all the fish exposed to such anesthetics had similar or lower concentrations than those detected at time zero (Kiessling et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Silver catfish exposed to EOO before handling had a better recovery profile of these parameters, as lower or similar concentrations were detected at 8 h compared to 0 h. A similar pattern was verified in the cortisol levels in Atlantic salmon following bath administration with benzocaine, MS-222, and isoeugenol. After 360 minutes, all the fish exposed to such anesthetics had similar or lower concentrations than those detected at time zero (Kiessling et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Stress response corresponds to an animal's attempt to maintain its homeostatic state (Barton, 2002;Kiessling et al, 2009). It involves the activation of neuroendocrine pathways, which promote catecholamine and corticosteroid (cortisol) release.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anaesthetic influence on fish stress (Limsuwan et al 1983b, Olsen et al 1995 and biochemical and haematological indices (Gomułka et al 2008, Velisek et al 2006) have also been reported. There is a little information on the pharmacokinetics of anaesthetics in fish (Meinertz et al 1996, Stehly et al 1998, Guénette et al 2007, Kiessling et al 2009). …”
Section: Introductionmentioning
confidence: 99%